Molecular Identification of Cryptococcus neoformans Isolates from House Environments of HIV-Infected Patients in an Urban Area, Indonesia: A First Report - Machrumnizar, Machrumnizar; Adawiyah, Robiatul; Natriana, Tjahjani; Imran, Darma; Muslim, Mohammad; Wellyzar, Sjamsuridzal; Wahyuningsih, Retno (Makara Journal of Science, 2022)
Cryptococcus neoformans isolates were previously obtained from pigeon droppings in Jakarta. This study aimed to determine another source of infection and describe the supporting niche of the fungus. The occurrence of C. neoformans was evaluated in 110 samples of decaying wood and leaves, tree hollow debris, dust, and bird droppings. Yeasts isolates were collected from 22 houses of HIV-infected patients. The isolates were identified based on culture characteristics, an assimilation test, and URA5 restriction fragment length polymorphism polymerase chain reaction. The spatial analysis was conducted in geographical information system to determine dominant house and environmental factors. Seven of the 120 isolates (5.83%) were identified as C. neoformans, corresponding to four (18.2%) houses. All isolates were from house environments of HIV-infected patients with cryptococcal meningitis. Spearman’s correlation analysis and McNemar’s test revealed a significant association between cryptococcosis in HIV-infected patients and their environment. The clinical and environmental isolates were 100% identical based on molecular techniques, indicating that the patients acquired cryptococcosis from the environment. The spatial analysis revealed that house dust, soil, and leaves were the dominant distribution factors in terms of estimating disease prevalence. This study demonstrates that the house environment is a source of infection for cryptococcosis.